Identifying Technical Descriptors for Restructuring of Development Plan Process using Delphi Technique - Varsha A. Dawle1, Sanjaykumar Sonar (International Journal of Advanced Science and Technology, 2020)
Restructuring of Development Plan Preparation and Implementation Process with a Paradigm Shift in Planning Approach is a pressing need for translating ever-increasing urban pressure and for achieving functional and sustainable urban planning outputs. Delphi technique is considered most suitable for identification of technical descriptors need to be addressed while restructuring development plan process based on responses from a small and selected group of experts. Outcome of this study helps the planners in deciding the factors need to be addressed while restructuring planning process. The study also concludes that as per experts views (i) Integrating Public Participation in planning and Implementation, (ii) Two level planning approach instead of single rigid development plan, (iii) Shorter plan period instead of current plan period of 20 years and 10 years (iv) Need based planning as per local requirements instead of standardized planning norms, (v) Fund allocation and strong financial planning for implementation of plan proposals, (vi) Plan implementation should be made statutorily obligatory and (vii) Identification of suitable implementation mechanism for each proposal are the main criteria need to be addressed while restructuring development plan Process.